Role of Cytochrome P450 in Prostate Cancer and its Therapy - Kaushik, Rishabh; Khan, Sheeza; Sharma, Meesha; Hemalatha, Srinivasan; Mueed, Zeba; Poddar, Nitesh K. (Current Enzyme Inhibition, 2020)
Prostate cancer has become a global health concern as it is one of the leading causes of mortality in males. With the emerging drug resistance to conventional therapies, it is imperative to unravel new molecular targets for disease prevention. Cytochrome P450 (P450s or CYPs) represents a unique class of mixed-function oxidases which catalyses a wide array of biosynthetic and metabolic functions including steroidogenesis and cholesterol metabolism. Several studies have reported the overexpression of the genes encoding CYPs in prostate cancer cells and how they can be used as molecular targets for drug discovery. But due to functional redundancy and overlapping expression of CYPs in several other metabolic pathways there are several impediments in the clinical efficacy of the novel drugs reported till now. Here we review the most crucial P450 enzymes which are involved in prostate cancer and how they can be used as molecular targets for drug discovery along with the clinical limitations of the currently existing CYP inhibitors.
Keywords: xenobiotic